2010
DOI: 10.1021/jp910594m
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in Carbon-Doped Zinc Oxide Systems

Abstract: We report spin polarized density functional calculations of ferromagnetic properties of a series of ZnO clusters and solid containing one or two substitutional carbon impurities. We analyze the eigen value spectra, spin densities and molecular orbitals, and induced magnetic moments for ZnC, Zn2C, Zn2OC, carbon substituted clusters ZnnOn (n=3-10, 12) and ZnO solid. The results show that the doping induces magnetic moment of the ∼2 µB in all the cases. All the systems with two carbon impurities show ferromagneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 37 publications
(54 reference statements)
1
36
0
Order By: Relevance
“…There are recent claims for RT ferromagnetism in carbon doped ZnO [22][23][24][25][26][27]. In line with the understanding of magnetism, as stated before, the question about the origin of magnetic moment does arise since there are no TM elements doped in the samples.…”
Section: Introductionmentioning
confidence: 71%
“…There are recent claims for RT ferromagnetism in carbon doped ZnO [22][23][24][25][26][27]. In line with the understanding of magnetism, as stated before, the question about the origin of magnetic moment does arise since there are no TM elements doped in the samples.…”
Section: Introductionmentioning
confidence: 71%
“…Besides the discovery of ferromagnetism in nonmagnetic cation doped semiconductors, the experimental researches demonstrated that high temperature ferromagnetism also can be obtained in nonmagnetic anion C-and N-doped ZnO and TiO 2 and C-doped GaN [10][11][12][13][14][15][16][17][18][19]. Furthermore, first-principles calculations reported that anion C or N substitutions in several oxides, sulfides and nitrides can induce ferromagnetism and the ferromagnetism is intrinsic [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…One of the widely investigated semiconductors is ZnO, at which magnetic formation depending on point defects has been revealed [1]. On the other hand, the findings point the ferromagnetism with doping of nonmagnetic elements as well, such as Al [5], Zn [5], Pt [5] and C [6] due to the p-p interactions in between 2p energy levels of cations (O, N, As etc.) and impurity band levels [5,6].…”
Section: Introductionmentioning
confidence: 99%